Prognostic impact of renal function in precapillary pulmonary hypertension. (7th October 2013) - Kaiser, R.; Seiler, S.; Held, M.; Bals, R.; Wilkens, H.
Abstract Background Impairment of renal function is associated with adverse outcome in various diseases. Patients with pulmonary hypertension (PH) show diminished cardiac function and organ perfusion. The aim of this study was to investigate the associations between renal function and both haemodynamic parameters and long‐term survival in patients with PH. Methods Blood was collected from 64 patients with PH (Dana Point class 1, 3 and 4) during right heart catheterization, and plasma was prepared. Creatinine, blood urea nitrogen (BUN), cystatin C, neutrophil‐gelatinase‐associated lipocalin (NGAL), fibroblast growth factor 23 (FGF‐23) and α‐Klotho levels were determined, and glomerular filtration rate (GFR) was estimated (eGFR). Parameters were evaluated using c‐statistics and dichotomized for survival analysis based on receiver operating characteristic curves. Results The median follow‐up time was 9.92 years with all‐cause mortality as the primary end‐point. Elevated BUN, cystatin C and creatinine levels were associated with decreased survival, with hazard ratios (HRs) of 3.237, 4.514 and 2.006, respectively, and equivalent performance according to c‐statistics. Estimating GFR by CKD‐EPI, MDRD and Cockcroft–Gault formulas resulted in HRs of 2.942, 2.694 and 3.306, respectively. Amongst these formulas, eGFR (Cockcroft–Gault) had the highest c‐statistics of 0.674. There was a correlation between BUN and both cardiac index (τ = −0.39) and pulmonary vascular resistance index (τ = 0.249), whereas eGFR (CKD‐EPI) was correlated with cardiac index (τ = 0.225). No correlations between either BUN or eGFR and right atrial pressure (RAP) were observed. NGAL, FGF‐23 and α‐Klotho had no prognostic impact or association with haemodynamic parameters. Conclusion Comparison of markers of renal function for prognosis in PH demonstrated superiority of creatinine, cystatin C and BUN over NGAL, FGF‐23 and α‐Klotho. Minor decreases in eGFR influence long‐term prognosis, and measurement of cystatin C levels might be useful to detect renal impairment in patients with a normal serum concentration of creatinine. Renal function in patients with PH is linked to cardiac index rather than RAP.